Adjuvant-Induced Arthritis in Guinea Pigs - Taranov, O.S. (Acta Naturae, 2016)
We propose a model of rheumatoid arthritis (RA) induced in outbred guinea pigs using a single subcutaneous injection of complete Freund’s adjuvant to the hind paw. Histological examination of this model shows fibrin deposition on the surface of the synovial membrane, leukocyte infiltration of the synovial membrane and adjacent tissues, proliferation of the granulation tissue, and emergence of angioid areas, characteristic of RA. The cell response appears as an increase in the plasma cell count and development of follicle-like lymphoid infiltrates; erosion of the articular surface of the cartilage, frequently with deep cartilage destruction over large areas; and epiphysiopathy. The high reproducibility of arthritis induction in this RA model has been demonstrated. The proposed model is promising for the assessment of anti-arthritis preparations and dosage regimens.